MARJIN PEMASARAN BERAS DI KECAMATAN LAEYA KABUPATEN KONAWE SELATAN - Fatma; Alwi, La Ode; Herdhiansyah, Dhian (Agrisurya, 2024)
This research aims to determine the marketing margin for rice in Laeya District, South Konawe Regency. The research method used in this study is the descriptive method. The sampling methods used in this research are purposive sampling and snowball sampling techniques. The data analysis used is marketing margin analysis. The research results show that: (1) there are two streams in the rice supply chain in Laeya District, South Konawe Regency. (2) Collectors in value chain streams I and II each have a margin value of Rp. 2,700/kg and Rp. 3,000/kg, large traders in value chain I have a margin of IDR 1,000/kg. Meanwhile, retailers in value chain streams I and II each have a margin value of IDR. 1,500/kg and Rp. 2,000/kg. The share of farmers in the value chain 1 is 43%. Meanwhile, marketing in the two-part value chain is efficient due to the large percentage of parts received by farmers, which is 50%.